Preventing Youth Crime in Scotland: The Practices of Early Intervention and Diversion under ‘Whole System Approach’ Implementation - Benbow, Nicola Louise (2019)
There is a great deal of importance placed upon the conceptual strategies of diversion and early intervention in the field of contemporary youth justice. Despite the centrality of these concepts, comparatively little attention has been paid to critically exploring how they are interpreted and enacted by professionals at the front line. This thesis investigates the meaning of the highly contested rationales of diversion and early intervention in relation to the current policy context of enacting a ‘Whole System Approach’ (WSA) to prevent youth crime in Scotland. Utilising a qualitative case study design, the field work involved: analysis of questionnaires following a scoping study, documentary analysis of protocols and guidance documents, multiple observations of meetings and events across three case study areas, and forty-two interviews with a range of youth justice professionals. This thesis makes a valuable contribution that is relevant for both professional and academic audiences. Firstly, the research brings considerable insight into the many intricacies and challenges involved for professionals working to prevent crime through early intervention and diversion. The research found that these strategies are conceptualised differently in practice, leading to ambiguity and variability in relation to local application. The thesis also considers the key implications arising from these differing conceptualisations, which raise some problematic issues of relevance to wider critical debates in youth justice. In particular, this thesis contributes to the academic literature through critically exploring the problems associated with responding to welfare concerns within a youth justice context, upholding children’s rights within a pre-statutory context, and the implications of allowing ample discretion and local experimentation in youth justice policy implementation. Lastly, the research also found some evidence of neo-liberal influence in the implementation of the WSA, serving as a reminder that multiple and complex discourses are consistently at play within the contemporary youth justice sphere